THE ROLE OF LEADERSHIP IN DEALING WITH FACTORS DRIVING CHANGE IN THE REVOLUTION 4.0 ERA - Mawarni, Irma Septria (Transpublika Publisher, 2022)
In over the world, including Indonesia's nations, is in the midst of the 4.0 industrial revolution. The success of an individual may be measured by the performance of the industry that is developing in this 4.0 age. However, an individual success is also determined by the leadership attitude maintained by the company's identity leader. This research aims to examine the role of leadership in coping with the 4.0 revolution's driving elements. This kind of paper is based on qualitative research and literature reviews. Analysis and research connected to books, papers, journals, or other relevant sources that are continuous with the title were conducted as part of the literature review for this topic. In the face of revolution 4.0, the paper concludes that there are four sorts of leadership styles to consider: